PENGARUH WORKLOAD TERHADAP TECHNOSTRESS PADA PEKERJA DI BIDANG INDUSTRI MULTIMEDIA KREATIF DIGITAL - Salsabila Nur Sadrina Jamaluddin; Arfin Nurma Halida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Rapid technological advancements including the emergence of tools such as Artificial Intelligence (AI) have greatly facilitated the work of professionals in the digital creative multimedia industry. However, the continuous pressure associated with technology usage can lead to "technostress," potentially causing physical and psychological issues for individuals. One factor potentially influencing technostress is workload specifically, the increasing complexity of job demands, ranging from responsibilities to time pressures, which impact an individual's psychological state in the workplace. This study aims to examine the effect of workload on technostress among workers in the digital creative multimedia industry. A quantitative method employing a linear regression approach was used. Data were collected from 160 participants via an online questionnaire, based on inclusion criteria requiring them to be workers in the digital creative multimedia industry who utilize AI. Data analysis was conducted using linear regression. The results indicate that workload has a significant positive effect on technostress (p < 0.001). The study concludes that workload exerts a moderate influence on technostress among workers in the digital creative multimedia industry.